Between universalistic and defensive forms of group attachment. The indirect effects of national identification on intergroup forgiveness. (1st September 2018) - Hamer, Katarzyna; Penczek, Marta; Bilewicz, Michał
Abstract: Usually, national identification is negatively related to intergroup forgiveness, but several studies found no relation between these variables. In order to examine this inconsistency, we conducted a study on a nationwide sample of Polish adults ( N  = 1006). We analyzed two ways in which national identification is connected to reconciliation: a general sense of belonging and openness to others (shared with supranational identifications, e.g., human) positively predicting intergroup forgiveness, and the more specific sense of ingroup distinctiveness and superiority (shared with collective narcissism and other defensive forms of identification), negatively predicting willingness to forgive. The results confirmed the dual character of national identification in relation to intergroup forgiveness and showed that collective narcissism and human identification are parallel suppressors of the relationship between national identification and intergroup forgiveness. Blind patriotism played only a minor role in this relationship, and constructive patriotism was unrelated to intergroup forgiveness. Highlights: We clarify mixed results on national identification's role in intergroup forgiveness. We propose dual-path model of national identification in intergroup forgiveness. National identity indirectly constrains forgiveness through collective narcissism. National identity indirectly enhances forgiveness through human identification.